(untitled) (SAARC Journal of Agriculture, 2018)
The aqueous extracts of neem Azadirachta indica, eucalyptus Eucalyptus globulus, telakucha Coccinia indica, mahogany Swietenia macrophylla and joba Hibiscus rosa-sinensis leaves were used to evaluate their toxicity and physiological effects on fruit fly Bactrocera cucurbitae (Diptera: Tephritidae) reared on ash gourd Benincasa hispida. The investigations were done with 1, 2 and 4% extracts and an untreated control. The toxicity of the extracts varied with plant species, concentration and exposure period. Among the treatments, neem revealed the most toxic effect as it showed the lowest LC50 and LC95 values as well as steepest slope of the concentration curve. The order of toxicity of the plants was neem> eucalyptus> telakucha> mehagony> joba. All the extracts reduced pupation, adult emergence, protein content in larval body and body weight of male and female flies. The highest reduction of protein, body weight of male and female flies, pupation and adult emergence were found with 4% neem extract. Among the tested extracts, 4% neem extract was found as the most effective botanical insecticide against B. Cucurbitae SAARC J. Agri., 15(2): 125-135 (2017)